Salvador González, José María. Ianua Coeli. María Mediadora de la Humanidad. Explicación doctrinal e iconografía. Valencia: Tirant lo Blanch, Humanidades, 2023, 232 p. [ISBN: 978-84-19588-88-3] - González Zymla, Herbert (Eikón / Imago, 2024)
Book review of Salvador González, José María. Ianua Coeli. María Mediadora de la Humanidad. Explicación doctrinal e iconografía. Valencia: Tirant lo Blanch, Humanidades, 2023, 232 p. [ISBN: 978-84-19588-88-3]